LOS POLYMORPHINAE, UN DIFERENTE TIPO ADAPTATIVO DE LOS PROTEROTHERIIDAE (MAMMALIA. LITOPTERNA) (Ameghiniana, 2013)
After the analysis of the material of Polymorphis Roth, 1899, and other similar forms of Mustersense age (Middle Eocene) of Patagonia, it seems fully justified to separate the group from the other Litopterna in, at least, a different subfamily, the Polymorphynae Simpson 1945; this is based on the degree of separation and divergence of the group frorn a11 other Liptoterna. A comparative study of Polymorpbis (as an arqueotype) with the Proterotheriinae is made; a more complete diagnosis for the subfamily Polymorphinae is also proposed. Short systematic consideration are incIuded to discuss the validity of the genera and species that Simpson (1945) incIuded in this subfarnily. Fina11y, the relations of the Polymorphinae with the other Proterotheriidae and the Macrauchenidae are discussed.